Energy of Cartesian product of Graphs - Prabha, R; Vadivukkarasi, PR (International Journal of Computer Sciences and Engineering, 2025)
An eigenvalue of a graph is an eigenvalue of its adjacency matrix. The energy of a graph is the sum of absolute values of its eigenvalues. Two graphs having same energy and same number of vertices are called equienergetic graphs. One might be interested to know, as to how the energy of a given graph can be related with the graph obtained from original graph by means of some graph operations. As an answer to this question we have considered the Cartesian product of two graphs. In this paper we obtain the eigenvalues and energy of Cartesian product of two graphs from the eigenvalue of the given graph.